The Role of Sulfation in Nematode Development and Phenotypic Plasticity - Igreja, Catia; Sommer, Ralf J. (Frontiers in Molecular Biosciences, 2022)
Sulfation is poorly understood in most invertebrates and a potential role of sulfation in the regulation of developmental and physiological processes of these organisms remains unclear. Also, animal model system approaches did not identify many sulfation-associated mechanisms, whereas phosphorylation and ubiquitination are regularly found in unbiased genetic and pharmacological studies. However, recent work in the two nematodes Caenorhabditis elegans and Pristionchus pacificus found a role of sulfatases and sulfotransferases in the regulation of development and phenotypic plasticity. Here, we summarize the current knowledge about the role of sulfation in nematodes and highlight future research opportunities made possible by the advanced experimental toolkit available in these organisms.